Innovative Industry: Environmental horticulture professionals’ perceptions on wildlife-friendly plants and a potential certification offering - Christine L. Krebs; Laura A. Warner; Lauri M Baker; Jaret C. Daniels; Adam Dale (Journal of Applied Communications, 2022)
Plants can improve people’s lives and mental health, but consumers have become increasingly concerned about the impact of plant production practices on the environment and wildlife. Previous research has not explored the interest and ability of plant producers and suppliers to provide wildlife friendly plant options for consumers. The University of Florida is considering the development of a wildlife-friendly plant certification to enhance production protocols for growers and connect consumers to sustainable plant options. This study explored perceptions of this certification through 11 in-depth interviews with environmental horticulture professionals. The study was guided by the following research questions: 1) What experiences do environmental horticulture professionals have with wildlife-friendly plants?, 2) What trends do environmental horticulture professionals see with consumers?, 3) What are the benefits and barriers to adopting this wildlife-friendly plant certification?, and 4) What communication strategies are needed to make this wildlife-friendly plant certification viable? Results indicate environmental horticulture professionals recognize the advantages of wildlife-friendly plants. However, the interviews revealed specific barriers to adoption and communication considerations that would impact certification diffusion. Implications of this research include a need for strategic programming regarding the wildlife-friendly plant certification and cohesive communication strategies among environmental horticulture organizations to educate professionals and consumers about wildlife-friendly plant options.
Keywords: Diffusion of Innovations; formative audience research; neonicotinoids; pollinators; wildlife-friendly plants